Evidence for a Role of ANAC082 as a Ribosomal Stress Response Mediator Leading to Growth Defects and Developmental Alterations in Arabidopsis. Issue 10 (12th September 2017) - Ohbayashi, Iwai; Lin, Chung-Yi; Shinohara, Naoki; Matsumura, Yoko; Machida, Yasunori; Horiguchi, Gorou; Tsukaya, Hirokazu; Sugiyama, Munetaka
Abstract : The existence of a ribosomal stress response in plant cells is revealed by molecular genetic studies that implicate ANAC082 as a crucial mediator of this pathway. Abstract: Ribosome-related mutants in Arabidopsis thaliana share several notable characteristics regarding growth and development, which implies the existence of a common pathway that responds to disorders in ribosome biogenesis. As a first step to explore this pathway genetically, we screened a mutagenized population of root initiation defective2 ( rid2 ), a temperature-sensitive mutant that is impaired in pre-rRNA processing, and isolated suppressor of root initiation defective two1 ( sriw1 ), a suppressor mutant in which the defects of cell proliferation observed in rid2 at the restrictive temperature was markedly rescued. sriw1 was identified as a missense mutation of the NAC transcription factor gene ANAC082 . The sriw1 mutation greatly alleviated the developmental abnormalities of rid2 and four other tested ribosome-related mutants, including rid3 . However, the impaired pre-rRNA processing in rid2 and rid3 was not relieved by sriw1 . Expression of ANAC082 was localized to regions where phenotypic effects of ribosome-related mutations are readily evident and was elevated in rid2 and rid3 compared with the wild type. These findings suggest that ANAC082 acts downstream of perturbation of biogenesis of the ribosome and may mediate a set of stress responses leading to developmental alterations and cell proliferation defects.